2020
DOI: 10.1002/biot.201900357
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 5‐Hydroxymethylfurfural to 2,5‐Furandicarboxylic Acid by a Syntrophic Consortium of Engineered Synechococcus elongatus and Pseudomonas putida

Abstract: 2,5-furandicarboxylic acid (FDCA) is one of the top platform chemicals that can be produced from biomass feedstock. To make the cost of industrial FDCA production compatible with plastics made from fossils, the price of substrates and process complexity should be reduced. The aim of this research is to create a CO 2 -driven syntrophic consortium for the catalytic conversion of renewable biomass-derived 5-hydroxymethylfurfural (HMF) to FDCA. Sucrose produced from carbon fixation by the engineered Synechococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…With this technique, this bacterium was modified to express hmfH and HMFT1 (encoding a HMF transporter) genes from C. basilensis, which allowed the production of 196 mM of FDCA with 78% yield. In a consortium approach, a Synechococcus elongatus strain engineered to export sucrose via CO 2 fixation was used as carbon source for a P. putida S12 strain modified for sucrose consumption and improved FDCA production [36]. Despite being innovative and having promise for reducing feedstocks costs within a biorefinery, this strategy only resulted in the production of ~4.6 mM of FDCA.…”
Section: 5-furandicarboxylic Acid (Fdca)mentioning
confidence: 99%
“…With this technique, this bacterium was modified to express hmfH and HMFT1 (encoding a HMF transporter) genes from C. basilensis, which allowed the production of 196 mM of FDCA with 78% yield. In a consortium approach, a Synechococcus elongatus strain engineered to export sucrose via CO 2 fixation was used as carbon source for a P. putida S12 strain modified for sucrose consumption and improved FDCA production [36]. Despite being innovative and having promise for reducing feedstocks costs within a biorefinery, this strategy only resulted in the production of ~4.6 mM of FDCA.…”
Section: 5-furandicarboxylic Acid (Fdca)mentioning
confidence: 99%
“…strain MP688) and HMF/furfural oxidoreductase (from Cupriavidus basilensis HMF14) were introduced into Raoultella ornithinolytica BF60 to improve the yield of FDCA to 93.6%. Further, Lin et al, 62 created a syntrophic consortium comprised of Synechococcus elongatus and Pseudomonas putida that led to a 100% conversion of HMF with 70% yield of FDCA. The utilization of the strain Acetobacter oleivorans S27 by Godan et al, 63 showed 100% conversion of HMF with 65% FDCA yield at an acidic pH of 5.5, establishing the wide range of pH tolerance of A. oleivorans S27 in the presence of HMF.…”
Section: 5-furandicarboxylic Acid (Fdca)mentioning
confidence: 99%
“…Both bacteria and fungi have long reported abilities of metabolizing furans, with conversion of HMF to HMF acid having been observed in, among others, Pseudomonas aeruginosa , Pseudomonas putida , Cupriavidus basilensis , Acetobacter rancens , Serratia liquefaciens , Serratia marcescens , Ureibacillus thermosphaericus , and Aspergillus sp. , Moreover, many wild-type and engineered organisms are able to catalyze the full oxidation of HMF to FDCA (Table ). …”
Section: Whole-cellmentioning
confidence: 99%
“…The high cost of HMF, for example, is derived from its difficult isolation and purification, its instability and tendency to undergo undesirable side processes (even during storage in the oily state), complex catalyst regeneration, low conversion selectivity (e.g., when using glucose as substrate), and the relatively high cost of associated solvents, catalysts, and carbohydrates (i.e., its own feedstock) . Lignocellulosics represent a sustainable and cheap source of hexoses for dehydration into HMF (to be used for conversion to FDCA), as well as a cheap and sustainable carbon source for microbial enzyme production/whole-cell conversion systems. One interesting study seeking to address the need for a cheap carbon source involved the use of a microbial consortium including a strain of P. putida engineered for the production of FDCA from HMF, and another strain, the photosynthetic organism S. elongatus , which provided P. putida with cheap and renewable primary substrates .…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation